INTERESTS OF THE SOCIAL RELATIONS SUBJECTS AND ITS COORDINATION IN THE TERRITORYS` ECONOMIC DEVELOPMENT PROCESS PROVIDING - Fufalko , I. Yu. (The actual problems of regional economy development, 2018)
The essence and interrelation of the social relations subjects’ interests that are represented in the corresponding territory are determined. The main interests include private interests of the population, economic entities and the state, as well as national (public) interests of the country as a whole. The definition of the public interests and their classification is clarified. Carriers, subjects of expression and representatives has been determined. Defined that the interests of various social relations subjects are often controversial, that requires to define approaches of their coordination. In the terms of the research, it is proposed to classify the subjects’ private interests into constructive and destructive ones. It allows to systematize existing approaches to the classification of various interests, harmonize their correlation with the peoples` general public interests and determine the role of each of them in ensuring the economic development of the territory. It has been determined that in a market economy constructive private interests are fundamental and determine the direction of society development. Though interests’ coordination should be realized according to their acceptability for all social relations participants. This will allow to achieve a special synergistic effect and maximize the welfare of a whole society.